Implementation of Academic Supervision by Principals in Elementary Schools - Piri, Meiske Feiny Sialom; Lengkong, Jeffry Sony Junus; Rotty, Viktory N. J.; Mongdong, Romi Junior (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to describe the implementation of academic supervision by elementary school principals. This study uses a qualitative approach and case study method. The location of the study was Tiniawangko State Elementary School in South Minahasa Regency. The sources of research data were informants of the principal, homeroom teacher and subject teacher. The data of this study were collected using interviews, observation, and documentation study techniques and processed using qualitative data analysis techniques of the interaction model. The results of the study indicate that the implementation of academic supervision by the principal is reflected in class visits and is oriented towards directives, collaboratives, and non-directives supported by factors originating from the principal, teachers, and school supervisors and inhibiting factors categorized as originating from teachers, the principal personally, and the school environment. Then, after discussing the results of the study, it was continued by compiling research conclusions and suggestions that were recommendatory in nature.